Determining factors of school dropout in the Huánuco region, Peru - Calero, Roberto (2023)
Objective. Determine the factors that explain school dropout in the Huánuco region, Peru, for the period 2010 - 2020. Methods. The research was of an applied type, it adopted an explanatory level and a non-experimental design. Two perspectives on school dropout (individual and institutional perspective) and data from the National Household Survey were used as a theoretical basis for the estimation of a logistic regression model. Results. It was found that the probability of school dropout increases: (i) regarding socioeconomic factors, if the student belongs to a household with a low socioeconomic level (2.985 pp.), lives in a single-parent family (0.234 pp.), has dropout parent’s basic education (4,013 pp.); (ii) regarding personal factors, if the student is older (0.801 pp.), or is male (0.856 pp.), or has the need to work (1.986 pp.). Conclusions. It is established that the socioeconomic factors of school dropout are: the socioeconomic level of the home, a history of dropout parents and the parental structure of the home. Meanwhile, the personal factors related to school dropout are age, sex and the need to work of the student.